Ultrastretchable and Self-Healing Double-Network Hydrogel for 3D Printing and Strain Sensor - Liu, Sijun; Li, Lin (ACS applied materials & interfaces, 2017)
On the basis of the thermoreversible sol-gel transition behavior of κ-carrageenan in water, a double-network (DN) hydrogel has been fabricated by combining an ionically cross-linked κ-carrageenan network with a covalently cross-linked polyacrylamide (PAAm) network. The κ-carrageenan/PAAm DN hydrogel demonstrated an excellent recoverability and significant self-healing capability (even when notched). More importantly, the warm pregel solution of κ-carrageenan/AAm can be used as an ink of a three-dimensional (3D) printer to print complex 3D structures with remarkable mechanical strength after UV exposure. Furthermore, the κ-carrageenan/PAAm DN hydrogel exhibited a great strain sensitivity with a gauge factor of 0.63 at the strain of 1000%, and thus, the hydrogel can be used as sensitive strain sensors for applications in robotics and human motion detection.